Predictors to Poor Quality of Life Among Patients with Heart Failure and Its Correlation with Their Medication Adherence: Finding for Healthcare Improvement and Follow-Up - Alkubati SA; Aleyadah HK; Alboliteeh M; Alharbi A; Alsaif B; Alshammari B; Balawi A (Patient Preference and Adherence)
Sameer A Alkubati,1,2 Homoud Khaled Aleyadah,1,3 Mohammad Alboliteeh,4 Abdulhafith Alharbi,5 Bandar Alsaif,6 Bushra Alshammari,1 Anas Balawi1 1Department of Medical Surgical Nursing, College of Nursing, University of Hail, Hail, Saudi Arabia; 2Department of Nursing, Faculty of Medicine and Health Sciences, Hodeidah University, Hodeidah, Yemen; 3Sharaf Primary Health Care, Hail Health Cluster, Hail, Saudi Arabia; 4Nursing Administration Department, College of Nursing, University of Hail, Hail, Saudi Arabia; 5Department of Psychiatric and Mental Health Nursing, College of Nursing, University of Hail, Hail, Saudi Arabia; 6Department of Public Health, College of Public Health and Health Informatics, University of Hail, Hail, Saudi ArabiaCorrespondence: Sameer A Alkubati, Department of Medical Surgical Nursing, University of Hail, Hail, Saudi Arabia, Tel +966506575284, Email alkubatisa@yahoo.comBackground: Understanding medication adherence and its relationship with quality of life (QoL) is essential for improving health outcomes in patients with heart failure (HF).Objective: This study aimed to investigate the predictors of poor quality of life and its relationship with medication adherence among patients with heart failure.Methods: A cross-sectional correlational study was performed on 229 patients with HF receiving care at the Cardiac Center of King Salman Specialist Hospital from March to June 2024. Data were collected using a structured questionnaire comprising patient demographics, the Minnesota Living with Heart Failure Questionnaire (MLHFQ) to assess QoL, and the General Medication Adherence Scale (GMAS) to measure medication adherence.Results: The mean medication adherence score among patients with heart HF was 17.53 ± 6.94. The level of adherence was moderate among most patients (47.2%), high (29.7%), and poor (23.1%). Regarding QoL, the mean total score for overall QoL was 42.16 ± 20.53. Specifically, the mean scores were 15.24 ± 8.65 and 10.53 ± 5.82 for the physical and emotional dimensions of QoL, respectively. More than half of the patients experienced poor QoL, while moderate QoL was observed in 31.9% and good QoL in 17% of patients. Furthermore, there were moderate negative correlations between medication adherence and physical QoL (r= − 0.51), emotional QoL (r = − 0.59), and overall QoL (r = − 0.59), all of which were statistically significant (p < 0.001).Conclusion: Moderate-to-poor levels of medication adherence and QoL were found among HF patients receiving care in Hail City. Therefore, interventions to improve medication adherence among patients with HF must be prioritized to enhance health outcomes and QoL. It is also crucial to address the factors that negatively influence medication adherence to overcome the barriers that hinder optimal medication adherence.Keywords: heart failure, quality of life, medication adherence, Saudi Arabia